HOW DO YOUNG PEOPLE SELECT INFORMATION TO PLAN A TRIP - ŢUGULEA, Oana; BOBALCA, Claudia; MAHA, Andreea; MAHA, Liviu (Revista de turism - studii și cercetări în turism, 2013)
The purpose of the research is to reveal the young tourists preferences in the process of planning a trip. Sources of information used, the utility of Internet/travel agencies in planning travel trip activities, preferred means of transportation and types of accommodation are investigated. As research methods, there used both qualitative and quantitative methods: focus group and survey. Internet is more used by young tourists in planning trips than travel agencies are. Internet is considered more useful in the documentation stage and when buying airline tickets. Young tourists are more influenced by friends when planning a trip. Young tourists prefer cars and planes as means of transportation for a trip and hotels and guesthouses as accommodation when traveling.